Cucurbit[n]uril-based fluorescent indicator-displacement assays for sensing organic compounds - Duan, Qunpeng; Chen, Ran; Deng, Su; Yang, Cheng; Ji, Xinxin; Qi, Gege; Li, Hui; Li, Xiaohan; Chen, Shihao; Lou, Mengen; Lu, Kui (Frontiers in Chemistry, 2023)
The widespread conversion of synthetic receptors into luminescent sensors has been achieved via the use of fluorescent-indicator displacement assays (F-IDAs). Due to their rigid structures and efficient binding affinities, cucurbit[n]urils, combined with a variety of fluorescent guests, have gained extensive utilization in fluorescent-indicator displacement assays for sensing non-fluorescent or weakly fluorescent organic compounds (analytes) in a selective and specific manner. This mini-review summarizes recent advances in the design of cucurbit[n]uril-based fluorescent-indicator displacement assays and discusses the current challenges and future prospects in this area.